Voluntary sector participation and individual health and welfare: Does it matter where?. (25th April 2022) - Handy, Femida; Sealey, Anthony
Abstract: Objective: Scholars have presented compelling evidence that participation in voluntary sector organizations (VSOs)—which is primarily motivated by the desire to help society—also benefits volunteers. The objective of this article is to determine whether and how these positive impacts vary across the type of VSO where individuals volunteer. Methods: We examine European Value Survey and World Value Survey data from 18 advanced industrial democracies using multilevel regression models to establish the link between VSO participation and three individual health and welfare (IHW) outcomes: an individual's self‐reported health status, financial satisfaction, and overall life satisfaction. Results: Our findings indicate (1) that the relationship between voluntary sector participation and positive IHW outcomes depends on the type of VSO where individuals volunteer and (2) that heterogeneous VSO exposure is also positively related to IHW. Conclusion: We emphasize that voluntary sector participation has heterogeneous impacts that variously determine outcomes depending on the type of VSO where an individual chooses to participate.